The Pattern of Communication in Community Groups Supported by Bandung City Government - Gani, Rita (Mediator: Jurnal Komunikasi, 2024)
The argument that the media influences our behavior both directly and indirectly is indeed a significant concern for mass media "connoisseurs." The Internet, in particular, is a powerful medium that provides a vast array of information. The use of the internet, whether through websites, social media, or other platforms, follows a basic concept of openness, allowing various types of information to be shared by and with many people. The position of the Kelompok Informasi Masyarakat  (hereinafter referred to as KIM) was confirmed based on the Minister of Communication and Information Regulation Number 8 of 2010 concerning the Development and Empowerment of Social Communication Institutions. It is a Community Information Group formed by the community, from the community and for the community, independently and creatively managing information and community empowerment to enhance added value. As a form of community empowerment, the existence of KIM is an alternative solution for raising awareness about the importance of group dynamics, especially in information exchange and fostering partnerships with various government agencies at the district and city levels. This case was analyzed using the theories of group communication, communication ethics, and communication media, which are integral to understanding the communication patterns within KIM.